Passive Bilingualism in the Iberian Peninsula - Jan Mrva (Universidad Pedagógica Nacional, 2018)
The purpose of this article is to describe passive bilingualism and the sociolinguistic situation in the Iberian Peninsula from the current perspective and to analyze the degree of passive bilingualism in this environment. In the first part, we introduce the reader to the problematic of passive bilingualism, and we attempt to define it using the contemporary theories made mainly in the field of Germanic languages. The practical part is dedicated to describing the hypothesis and the methodology that we applied when creating the questionnaire. In this part, we also include the demographic data of the respondents who completed the survey. Next is the analysis of the linguistic material, where we analyze: the number of correct and incorrect answers and the determination of success in different parts of the questionnaire; the possible causes of the wrong answer; the general level ofpassive comprehension in Galician, Catalan, Basque and Portuguese. In the discussion, we summarize, above all, the most important results of the analysis. Finally, we report on the pedagogical possibilities of the used languages.